Value of time: Speeding behavior and gasoline prices - Hendrik Wolff (Institute for the Study of Labor (IZA), 2012)
Do drivers reduce speeds when gasoline prices are high? Previous research investigating this energy conservation hypothesis produced mixed results. We take a fresh look at the data and estimate a significant negative relationship between speeding and gasoline prices. This presents a new methodology of deriving the 'Value of Time' (VOT) based on the intensive margin (previous VOT studies compare across the extensive margin) which has important advantages to circumvent potential omitted variable problems. While our VOT is 50% of the gross wage rate, we show that previous stated preference estimates are likely downward, whereas previous revealed preference estimates are systematically upward biased. We discuss implications, as VOT today is a key parameter in economics and policy.
Keywords: D70; J17; K32; Q26; R41; 330; value of time; speeding; gasoline price